2006
DOI: 10.1002/chem.200600616
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of Chiral 1,1′‐Binaphthalenes by the Asymmetric Suzuki–Miyaura Reaction: Dramatic Synthetic Improvement by Simple Purification of Naphthylboronic Acids

Abstract: Naphthylboronic acids prepared as reported in the literature are contaminated with HCl. A very simple purification prior to their use in Suzuki-Miyaura couplings has been found to be crucial, rendering efficient some reactions that had been reported in the literature either to fail or to give extremely poor yields. With this improvement, parent boronic acids can be used instead of esters at moderate temperatures, and bromo derivatives can be used instead of iodo derivatives. Convenient access to chiral sterica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(42 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…[3,4] Recently, Bermejo et al reported a novel asymmetric catalytic system that promotes the SuzukiMiyaura biaryl coupling with excellent enantioselectivity. [5] Although pioneering strides have been made, the development of highly enantioselective catalyst systems with wide substrate tolerance and acceptable catalytic activity still remains a major challenge.…”
mentioning
confidence: 99%
“…[3,4] Recently, Bermejo et al reported a novel asymmetric catalytic system that promotes the SuzukiMiyaura biaryl coupling with excellent enantioselectivity. [5] Although pioneering strides have been made, the development of highly enantioselective catalyst systems with wide substrate tolerance and acceptable catalytic activity still remains a major challenge.…”
mentioning
confidence: 99%
“…In order to provide an alternative to the rather sensitive boronic esters, they reported a purification procedure of naphthylboronic acids [98] that improved dramatically the efficiency of the catalytic reactions (from traces of coupling products before purification to up to 95% yield) under the same conditions than those reported by Cammidge et al [50]. During this study, precursor was also looked into.…”
Section: Page 26mentioning
confidence: 90%
“…Scheme 3.20 -Asymmetric biaryl coupling with ligands 2, 31 and 32[98]. Scheme 3.24 -Heterogeneous asymmetric biaryl coupling in water[106].Scheme 3.26 -Asymmetric biaryl coupling with ligands 45a-c [109].Scheme 3.28 -Dynamic asymmetric Suzuki coupling with ligand 52[48].…”
mentioning
confidence: 99%
“…2-Bromo-3-methylbenzoyl chloride and 4-bromo-3-methylbenzoyl chloride were prepared through the reaction of the corresponding carboxylic acids with oxalyl chloride in toluene. The regioselectively protected cellulose derivative CeATr [54], 2-methylnaphthalen-1-ylboronic acid 8a [55], and 2-methoxylnaphthalen-1-ylboronic acid 8b [55] were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%